The Calorie Consumption Puzzle in India: An Empirical Investigation - Deepankar Basu; Amit Basole (University of Massachusetts, Department of Economics, 2012)
Over the past four decades, India has witnessed a paradoxical trend: average per capita calorie intake has declined even as real per capita monthly expenditure has increased over time. Since cross sectional evidence suggests a robust positive relationship between the two variables, the trend emerges as a major puzzle. The main explanations that have been offered in the literature to address the puzzle are: rural impoverishment, relative price changes, decline in calorie needs, diversification of diets, a squeeze on the food budget due to rising expenditures on nonfood essentials, and decline in subsistence consumption (due to commercialization). Using a panel data set of 28 Indian states and the national capital territory of Delhi over four time periods (199394, 199900, 200405 and 200910), we test for these alternative explanations. Our results suggest that the puzzle can be explained by a combination of the following three factors: a food budget squeeze, declining subsistence consumption and diversification of diets. We do not find evidence of a strong effect of declining calorie needs. JEL Categories: O1, I30
Keywords: O1; I13; 330; calorie consumption puzzle; India; panel data